Interrelation between emotional competence and leadership as components of pedagogical activity (Pedagogy of Higher and Secondary Education, 2012)
Krupsky О., Kiba K. Interrelation between emotional competence and leadership as components of pedagogical activity.The article is devoted to a problem of interrelation of emotional intelligence and leadership, their influence on pedagogical activity, and also communication identification between emotional intelligence of teachers and pupils of averages and higher educational institutions.
Keywords: leadership; motivation; emotional intelligence; competences; styles of emotional leadership